Kutaja Kshara- A Comprehensive Literature Review (AYUSHDHARA, 2021)
The word ‘Kshara’ can be derived from either of the two roots, Ksarana or Kshanana. Ksharana means to dislodge, to melt away and Kshanana means to kill or to destroy. The literal meaning of the word ‘Kshara’ is the substance which is corrosive, caustic, pungent, saline and acrid in its properties. This Kshara Kalpana is known to have a wide scope in Shalya Tantra branch of Ayurveda. Because of this wider scope many research works are at present undertaken in order to treat many ailments and avoid few surgical procedures. Apamarga Kshara is mainly used in practice and many experiments are already done on the same, in order to study the properties and effects of other drugs or Ksharas, one such drug is chosen here i.e., Kutaja. Ksharas are superior to Shastras, Anushastras, because of their capability to perform Chedana (excision), Bhedana (incision), and Lekhana (scraping). It alleviates all the three Doshas. Ksharas can be used where Shastra Chikitsa is contra-indicated or where instruments cannot be used i.e., Marmasthana, for women, children or on those who are afraid of surgery. Acharya Susruta, while describing the process of Kshara extraction has mentioned 23 drugs and Kutaja is first and foremost drug. There are no direct references of properties and extraction of Kutaja Kshara in classics and other compilation done on the same were also not found while searching through internet. Present paper throws light on the complete description of Kutaja as a Kshara and preparation of Kshara Sutra mentioned in different texts of Ayurveda.